IMPLEMENTASI METODE USER CENTERED DESIGN DALAM PERANCANGAN APLIKASI PEMBELAJARAN VLAN & INTER-VLAN ROUTING - Anthonio Febrianto Patulak; Joko Purwadi; Theresia Herlina R. (Universitas Kristen Duta Wacana, 2015)
This research aims to make learning application materials VLANs and Inter-VLAN Routing with User-Centered Design (UCD) methods. System was evaluated by involving students, to evaluate the level of interest and ease students' learning. The results of feedback given by the participants back to the interface implemented learning applications. In addition, the authors also do a hypothesis test to determine whether the designed application has improved the understanding of learning for the user or not. Based on the results of usability testing using self-reported metrics showed 72% of participants agreed that the learning system useful, 74% of participants were satisfied with the learning system that has been made, 62% of participants agreed that the learning system is easy to use, and 64% of participants agreed that the learning system provides ease of learning.